PELATIHAN MITIGASI BENCANA BANJIR, UPAYA PENGOBATAN MANDIRI, DAN KONSELING TRAUMA HEALING PASCA BENCANA DI DESA PEKAUMAN ULU KABUPATEN BANJAR KALIMANTAN SELATAN - Muhammad Ikhwan Rizki; Fadlilaturrahmah Fadlilaturrahmah; Anna Khumaira Sari (Jurnal Bakti untuk Negeri, 2021)
South Kalimantan in early 2021 experienced the largest flooding in the last 50 years. Data in Banjar Regency shows that there are 27,368 houses, 2 bridges, 5 places of worship and 9 schools in 207 villages from 19 sub-districts in Banjar Regency that are affected. Pekauman Ulu Village was affected by flooding with a large potential for flooding. The purpose of this community service is to improve community skills in disaster mitigation, post-disaster counseling, and community knowledge in efforts to self-medicate in disaster situations. The service method carried out is through counseling, training, and distributing booklets related to self-medication. The results of the service activities were evaluated through the presence of the community, the results of the pretest and posttest, as well as the testimonies of the participants who attended. The data were analyzed descriptively and presented in the table. The service that has been carried out was attended by 48 participants, participants actively asked questions and were involved in discussions. Based on the results of the pretest and posttest, there was an increase in knowledge related to disaster mitigation from 49.77% to 83.55%, basic trauma healing abilities from 54.67% to 84.44%, and understanding of self-medication from 38.22% to 85. 77%. The conclusion from community service shows that there is an increase in knowledge related to disaster mitigation, basic trauma healing abilities, and understanding of self-medication